2012
DOI: 10.1177/0192623312457271
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae-mediated Endocytosis of Intratracheally Instilled Gold Colloid Nanoparticles at the Air–Blood Barrier in Mice

Abstract: Endocytosis is the primary mechanism by which nanoparticles are translocated over the alveolar epithelium. The purpose of this study was to elucidate the association between endocytosis and the translocation of nanoparticles at the air-blood barrier (ABB). Gold colloid particles (diameter, 20 nm) were intratracheally instilled into male ICR mice. Fifteen minutes after instillation, localized accumulation of agglomerated gold particles was observed in the cytoplasm of macrophages, on the surface of alveolar epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…The uptake of Au NPs via caveolinmediated endocytosis has already been observed in previous studies [23,51,57,58]. These studies, however, used different models and differently modified and sized particles.…”
Section: Cellular Np Uptakementioning
confidence: 52%
See 1 more Smart Citation
“…The uptake of Au NPs via caveolinmediated endocytosis has already been observed in previous studies [23,51,57,58]. These studies, however, used different models and differently modified and sized particles.…”
Section: Cellular Np Uptakementioning
confidence: 52%
“…For example, Hao and colleagues found a m cd-mediated uptake inhibition of 10 nm cysteincy5-coated Au NPs in HeLa cells [51]. The results of an in vivo study by Naota and colleagues showed localization of 20-nm plain, colloidal Au NPs in caveolin-1-positive stained vesicles in air-blood barrier cells in mice [58]. In a previous study with A549 cells and 15-nm sized plain and polyethylene glycol-coated Au NPs we found a m cd-mediated inhibition after 1 h of 86 and 97%, respectively [33].…”
Section: Cellular Np Uptakementioning
confidence: 99%
“…Caveolae-mediated endocytosis is also considered to be one of the pathways for the translocation of nanoparticles in the air–blood barrier [26]. Caveolin-1 protein plays a role in the regulation of caveolar invagination and the formation of caveolae, which is one form of the endocytic vesicle [19, 25, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Within AJ zona occludins establish links to the tubulin-based cytoskeleton, as well as actin; Cav-1 appears to be necessary for retrieval of these junctional proteins[122]. Caveolar-type MLR are also involved in endocytosis by epithelial cells[123], which in some instances involves Rab11 and the tubulin-based cytoskeleton[124]. Additional findings indicate that basolateral membranes may contain different Cavs[125, 126] and lipid components[127, 128] than those of the apical membranes of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%